2009
DOI: 10.1111/j.1751-1097.2008.00454.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Chronic Exposure to Artificial UVB Radiation on the Survival and Reproduction of Daphnia magna Across Two Generations

Abstract: We examined the effects of daily (chronic) exposure to artificial UVB radiation on the survival and reproduction of Daphnia magna over two generations. Control and experimental animals in each generation (parental and F1) were exposed to 16 h of UVA radiation and photosynthetically active radiation daily. In addition, experimental animals were exposed to 6 h of UVB during the middle of the light period. Survival and reproduction were followed for 12 days for each individual. Survival and production of F1 were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 23 publications
2
20
0
Order By: Relevance
“…In contrast to the reduced survival reported as a consequence of UV‐B stress on cladoceran species (Connelly et al., 2015; Huebner, Loadman, Wiegand, Young, & Warszycki, 2009), low doses of UV‐A radiation may not significantly affect the life span of Daphnia , although reproduction could be affected (Zellmer, 1998). In this case, the structural equation model analysis revealed that all effects of UVR on the per capita fecundity were likely indirect effects for both lineages (Figure 5, Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the reduced survival reported as a consequence of UV‐B stress on cladoceran species (Connelly et al., 2015; Huebner, Loadman, Wiegand, Young, & Warszycki, 2009), low doses of UV‐A radiation may not significantly affect the life span of Daphnia , although reproduction could be affected (Zellmer, 1998). In this case, the structural equation model analysis revealed that all effects of UVR on the per capita fecundity were likely indirect effects for both lineages (Figure 5, Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…enzymatic repair have been shown to be temperature dependent (8,9). Despite these protective mechanisms, elevated UVR has been shown to have deleterious effects on survival and reproduction in zooplankters such as Daphnia (10–13). These include direct effects due to DNA disruption (14), organ damage (15,16) and changes in physiology (17), as well as indirect effects such as reduced nutrition and extended exposure to suboptimal temperatures due to longer periods deeper in the water column (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…parental exposure to UV-B decreased survival and fitness of Daphnia offspring upon exposure to UV-B (Huebner et al 2009). Contrary to the results for Daphnia, however, parental exposure to UV-B did not increase ROS damage in offspring of guppies that were exposed to UV-B after birth.…”
Section: Controlmentioning
confidence: 99%